COL1A1/2 Pathogenic Variants and Phenotype Characteristics in Ukrainian Osteogenesis Imperfecta Patients - Zhytnik, Lidiia; Maasalu, Katre; Pashenko, Andrey; Khmyzov, Sergey; Reimann, Ene; Prans, Ele; Kõks, Sulev; Märtson, Aare (Frontiers in Genetics, 2019)
Osteogenesis Imperfecta (OI) is a hereditary bone disorder caused by defects of type I collagen. Although up to 90% of patients harbor pathogenic variants in the COL1A1/2 gene, which codes for collagen α1/2 chains, the spectrum of OI genotypes may differ between populations, and there is academic controversy around OI genotype-phenotype correlations. In the current study, 94 Ukrainian OI families were interviewed. Clinical and genealogical information was collected from patients in spoken form, and their phenotypes were described. To identify the spectrum of collagen I pathogenic variants, COL1A1/2 mutational analysis with Sanger sequencing was performed on the youngest affected individual of every family. Of the 143 patients investigated, 67 (46.85%) had type I OI, 24 (16.78%) had type III, 49 (34.27%) had type IV and III (2.10%) had type V. The mean number of fractures suffered per patient per year was 1.32±2.88 (type I 0.50±0.43; type III 3.51±6.18; type IV 1.44±1.77; and type 5 0.77±0.23). 87.23% of patients had skeletal deformations of different severity. Blue sclera, Dentinogenesis Imperfecta and hearing loss were present in 87%, 55% and 22% of patients, respectively. COL1A1/2 pathogenic variants were harbored by 60 patients (63.83%). 27 pathogenic variants are described herein for the first time. The majority of the pathogenic variants were located in the COL1A1 gene (76.19%). Half (49.21%) of the pathogenic variants were represented by structural variants. OI phenotype severity was highly correlated with type of collagen I defect. The current article presents an analysis of the clinical manifestations and COL1A1/2 mutational spectrum of 94 Ukrainian OI families with 27 novel COL1A1/2 pathogenic variants. It is hoped that this data and its analysis will contribute towards the increased understanding of the phenotype development and genetics of the disorder.